Consumer Acceptance of a New Brand of Telemea Cheese. A Descriptive Sensory Analysis - Corina A. MARES; Diana E. DUMITRAȘ DUMITRAȘ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2023)
Descriptive sensory analysis may reveal information necessary to improve or maintain product quality and to understand consumers buying intentions. This study aimed to understand, by means of using descriptive sensory analysis, the consumer acceptance of a new brand of white sheep cheese ‘Telemea’ and to reveal its position in respect to competitive products. The evaluation was performed by a group of panelists who assessed four brands. The appearance-exterior, appearance-interior, odour, taste, and consistency were evaluated according to the DLG 5-point scheme as a descriptive sensory analysis method. Data were analyzed using descriptive statistics and statistical tests. Further, the principal component analysis was used to better understand the differences and similarities between the four brands belonging to the same type of cheese. Results indicate that consumers highly appreciate the new brand and show high degree of acceptance compared to the other brands. The results of the descriptive sensory analysis represent the starting point in developing marketing strategies for producers of cheese, in close connection with consumers’ perceptions. Developing marketing strategies that take into account consumer preferences is vital for a product to succeed on the market in the long term.